Mandume: rastros da diáspora na reconstrução de memórias e identidades negras no rap - Lucianna Sousa Furtado Brito (2019)
The purpose of this dissertation is to explore what the orality and visuality of the music video Mandume (Emicida feat. Drik Barbosa, Amiri, Rico Dalasam, Muzzike and Raphão Alaafin, directed by Gabi Jacob, 2016) reveal about the violence of racial relations in Brazil. The research is based on the assumption that black music, precisely because of its historically silenced voices and marginalized knowledge traditions, can present potentially counter-hegemonic perspectives on political and social matters, reconstructing black collective memories and identities. The music videos verbal and visual enunciations were approached as witness accounts of the current black genocide in our society, considering rap records as historical sources concerning racial relations. The discussion addressed the belonging relations in black diaspora on its search for self-definition in representational processes; the consolidation of racialized social places on the historical conditions which structure cultural imaginaries; the hierarchical relations between literate rationality and popular ways of thinking, making politics and communicating; and the appropriation of identity and epistemological positionality through intersectionality as critical intervention on structural axes of power and subordination. The research dialogued with Mandume through stylistic analysis and the contributions of Visual Studies, approaching its formal elements together with the cultural dimensions that permeate the encounter between the observer and the visual materiality. Guided by the notions of metapicture, image-text and the performative effects of the acts of seeing, this combination emphasized visual experience as a culturally established social practice, an interaction conditioned by the subjects world views and cultural imaginaries. The research showed that the genocide against the black population develops its continuity through its epistemological dimension, on the field of knowledge, silencing ways of thinking, making politics and communicating that constitute and are constituted by the black social movements. Besides highlighting the epistemic sphere of racist violence, it showed its structural character, impacting all forms of sociability and interacting with other power categories. This way, the analysis revealed that Mandumes self-referentiality concerns not only the racialized representational regimes, but also the epistemicide against black intellectualities, claiming the legitimacy of these knowledge traditions